Pengaruh penerapan metode tebak gambar budaya terhadap pemahaman kebudayaan nusantara siswa pada pembelajaran Ips kelas 4 SD N Krikilan 1 - Zaen, Salsabela Makarima; Rukayah, Rukayah; Supianto, Supianto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to determine the influence of the application of cultural picture guessing method on students’ understanding of Nusantara culture in social studies learning grade IV SDN Krikilan I, determine how much influence the application of cultural picture guessing method on understanding of the Nusantara culture, and describe the steps of applying the cultural picture guessing method on the Nusantara culture. This study used a quasi-experimental research method and one-group time-series design. The research results are there is an influence of the application of cultural picture guessing method on students' understanding of the Nusantara culture in social studies grade IV SD N Krikilan I by the whole results of paired t test as sig. (2-tailed) = 0.000 <0.05, percentage of overall student understanding from the average percentage of understanding of each indicator from 35.70665% to 65.8654%. (3) the percentage of syntax implementation is 100% with all 16 syntax implemented. The results of this study can be used as a study in the repertoire of educational science and used as a reference for further research and it is hoped that this research can help improve students' understanding of Nusantara culture.